3 целых 1 / 8 + 1 целая 3 / 4 ) × Х = 2 целых 1 / 6
( ( 3 * 8 + 1 ) / 8 + ( 1 * 4 + 3 ) / 4 ) * х = ( 2 * 6 + 1 ) / 6
( ( 24 + 1 ) / 8 + ( 4 + 3 ) / 4 ) * х = ( 12 + 1 ) / 6
( 25 / 8 + 7 / 4 ) * х = 13 / 6
( 25 / 8 + 7 * 2 / ( 4 * 2 ) ) * х = 13 / 6
( 25 / 8 + 14 / 8 ) * х = 13 / 6
39 / 8 * х = 13 / 6
39 * х * 6 = 8 * 13
х = 8 * 13 / ( 39 * 6 )
х = 2 * 4 * 13 / ( 13 * 3 * 2 * 3 )
Числитель и знаменатель в дроби сокращаем на 13 и 2, тогда
х =1 * 4 * 1 / ( 1 * 3 * 1 * 3 )
х = 4 / ( 3 * 3 )
х = 4 / 9
ответ: х = 4 /
3 целых 1 / 8 + 1 целая 3 / 4 ) × Х = 2 целых 1 / 6
( ( 3 * 8 + 1 ) / 8 + ( 1 * 4 + 3 ) / 4 ) * х = ( 2 * 6 + 1 ) / 6
( ( 24 + 1 ) / 8 + ( 4 + 3 ) / 4 ) * х = ( 12 + 1 ) / 6
( 25 / 8 + 7 / 4 ) * х = 13 / 6
( 25 / 8 + 7 * 2 / ( 4 * 2 ) ) * х = 13 / 6
( 25 / 8 + 14 / 8 ) * х = 13 / 6
39 / 8 * х = 13 / 6
39 * х * 6 = 8 * 13
х = 8 * 13 / ( 39 * 6 )
х = 2 * 4 * 13 / ( 13 * 3 * 2 * 3 )
Числитель и знаменатель в дроби сокращаем на 13 и 2, тогда
х =1 * 4 * 1 / ( 1 * 3 * 1 * 3 )
х = 4 / ( 3 * 3 )
х = 4 / 9
ответ: х = 4 /
Пошаговое объяснение:
0,6у+4=0,2у
0,6y-0,2y=-4
0,4y=-4
y=-4:0,4
y=-10
2)
4-0,5х=0,3х
0,3x+0,5x=4
0,8x=4
x=4:0,8
x=5
3)
1,5=1,2-0,3z
-0,3z=1,5-1,2
-0,3z=0,3
z=-1
4)
-0.6+1.6a=0.4a
1,6a-0,4a=0,6
1,2a=0,6
a=0,6:1,2
a=0,5
5)
-3х+7,5=-0,5х
3x-0,5x=7,5
2,5x=7,5
x=7,5:2,5
x=3
6)
1,9-1,5z=0.1-0.5z
1,5z-0,5z=1,9-0,1
z=1,8
7)
0,8с-0,1=-0,2с
0,8c+0,2c=1
c=1
8)
-с+0,6=-0,7
c=0,6+0,7
c=1,3
9)
1,6=0,4z-0.8
0,4z=1,6+0,8
0,4z=2,4
z=2,4:0,4
z=6
10)
1.3-0.6c=0.2-0.5c
0,6c-0,5c=1,3-0,2
0,1c=1,1
c=1,1:0,1
c=11